Regional factors as major drivers for microbial community turnover in tropical cascading reservoirs - Vieira, Helena Henriques; Bagatini, Inessa Lacativa; de Moraes, Guilherme Pavan; Freitas, Roberta Mafra; Sarmento, Hugo; Bertilsson, Stefan; Vieira, Armando Augusto Henriques (Frontiers in Microbiology, 2022)
The turnover of microbial communities across space is dictated by local and regional factors. Locally, selection shapes community assembly through biological interactions between organisms and the environment, while regional factors influence microbial dispersion patterns. Methods used to disentangle the effects of local and regional factors typically do not aim to identify ecological processes underlying the turnover. In this paper, we identified and quantified these processes for three operational microbial subcommunities (cyanobacteria, particle-attached, and free-living bacteria) from a tropical cascade of freshwater reservoirs with decreasing productivity, over two markedly different dry and rainy seasons. We hypothesized that during the dry season communities would mainly be controlled by selection shaped by the higher environmental heterogeneity that results from low hydrological flow and connectivity between reservoirs. We expected highly similar communities shaped by dispersal and a more homogenized environment during the rainy season, enhanced by increased flow rates. Even if metacommunities were largely controlled by regional events in both periods, the selection had more influence on free-living communities during the dry period, possibly related to elevated dissolved organic carbon concentration, while drift as a purely stochastic factor, had more influence on cyanobacterial communities. Each subcommunity had distinct patterns of turnover along the cascade related to diversity (Cyanobacteria), lifestyle and size (Free-living), and spatial dynamics (particle-attached).